The Influence Of Service Quality Dimensions On Patient Ratings In Google Reviews Based On Text Mining (Survey Study At Hasna Medika Cirebon Hospital) - Meti Linawati; Kosasih; Rulia; Farida Yuliaty; Vip Paramarta (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to examine the effect of service quality dimensions on patient ratings on Google Review using a text mining approach at Hasna Medika Hospital, Cirebon. An descriptive-verificative quantitative design was employed using secondary data derived from patients’ online reviews. The analytical procedure included text preprocessing (cleaning, tokenizing, and normalization), keyword mapping into the five SERVQUAL dimensions (Reliability, Assurance, Tangibles, Empathy, and Responsiveness), and quantification of dimensional frequency as independent variables. Multiple linear regression analysis was conducted to test both simultaneous and partial effects on patient ratings as the dependent variable. The findings reveal that, simultaneously, the five service quality dimensions significantly influence patient ratings. Partially, Tangibles and Responsiveness demonstrate positive and significant effects, while Reliability and Assurance show significant negative effects. Empathy does not exhibit a significant influence. The coefficient of determination (R² = 0.323) indicates that the model explains 32.3% of the variance in patient ratings. These results suggest that digital patient reviews analyzed through text mining provide a data-driven approach for evaluating hospital service quality and offer managerial implications for strengthening patient-centered care strategies.